Некоторые особенности функционирования гражданских советов в странах англосаксонской и романо-германской правовой семьи - Krainii, Pavlo (My University, 2022)
The legal regulation of the activities of public councils, as a type of advisory bodies, may be regarded as a response to the inability of basic administrative procedures, as well as procedures of adopting administrative or normative acts to ensure the appropriate level of public participation in the decision-making process. On the other hand, the lack of legislative regulation of certain tools that stipulate citizens’ participation in government’s decision-making will indicate the absence of state’s desire to establish a social dialogue with its citizens with the aim of involving a broad range of stakeholders to make decisions that would meet both private and public interests. The studies of certain peculiarities that concern the functions of advisory bodies (public councils) in different countries have been carried out with a due regard to their inner features, the specifics of a legal system, and the level, at which citizens’ right to participate in managing the state affairs is ensured. The comparison of the peculiarities of the functions of such councils completely de pends on the type of a legal family the state belongs to. Selected for the above compari son Anglo-Saxon and Roman-Germanic legal families comprise the countries that have constituted a solid basis for the western legal tradition. These are the countries that laid foundation of the present-day system of legal institutions of public and administrative law. On the level of their Constitutions, they have enshrined a new generation of rights and freedoms, among which are the right to participate in management of state affairs, the right to access public information, the right to a certain legal procedure (envisaged by law), etc. The article under studies carries out an overall analysis of the activities and peculiarities of public councils’ functioning within the above mentioned legal families in order to determine the level of their significance and efficiency in terms of administrative-legal regulation
On some peculiarities of the functions of public councils in the countries of anglo-saxon and roman-germanic legal families
Keywords: advisory committee; advisory councils; Federal Advisory Committee Act; non-departmental public bodies